The role of environmental graphic design in place attachment of customers in a selected restaurant - Cultura, Glenn; Juarez, Lizza M.E. (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
The Micro, Small, and Medium Enterprises (MSME) sector holds the key to an inclusive recovery of the country (UN Philippines, 2020), addressing the negative effects of the COVID-19 pandemic on local businesses. Interior design can be a tool in marketing the products and services of these businesses (Gibbs, 2005), and play a significant role in reviving the economy. Environmental graphic design (EGD) which functions as a guide, sources of information, and influencers of experiences of the people in interior spaces (Niron, 2009) can prove to be a solution to alleviate these negative effects. With this, the purpose of the study was to determine the EGD systems implemented in a selected local quick service restaurant in Metro Manila, discuss its role in the dine-in customers’ place attachment, and determine its component that showed most influence. The study followed an exploratory sequential design, sampling 25 dine-in customers of the restaurant for the online survey, with three (3) participating in the follow-up interview. The results of the study suggest that the interior branding component of EGD showed the most influence on dine-in customers’ place attachment. Information system component also showed positive influence, with the focus on menu board design. However, wayfinding and signage showed no significant influence on the place attachment of regular dine-in customers. Furthermore, three key characteristics of EGD were found to be crucial in place attachment of dine-in customers namely: personal relevance of graphics to customers, consistency of the application of the restaurant’s branding, and design composition and placement of environmental graphics in the interior space. These results would help interior designers formulate strategies benefitting both the local businesses and the users of the space.
Thesis
Includes bibliographical references (pages 63-71)
Keywords: Restaurants -- Philippines -- Decoration -- Bibliography; Environmental graphic design